Product development of pasteurized ready-to-cook marinated white shrimp Litopenaeus vannamei in green curry paste - Mohamed, Nor Salasiah Binti (Chulalongkorn University, 2015)
Thesis (M.Sc.)--Chulalongkorn University, 2012